Impact of Curricular Changes Upon Professional Staff Training Efforts. - Seiler, Robert E.; Label, Wayne A. (The Accounting Review, 1974)
Abstract This article focuses on changes in accounting curricula at the university level in the U.S. The curricula is being modified to keep abreast of the profession's needs, but the full extent of that change and its impact upon other professional activities are difficult to measure. The purpose of this article is to identify several major trends presently manifested in university curricula, to relate these to major changes in staff training and professional development activities, and to suggest conclusions concerning the impact of one upon the other. A two-part study was undertaken to gather the data from which these conclusions are drawn. The first part of the study was a detailed analysis of the staff training programs and activities of 10 national public accounting firms, covering a 6-year period, 1966-72. The second consisted of an opinion survey of 150 leading college and university professors throughout the United States, undertaken in an effort to identify their perception of changes in accounting education.